Teacher Empowerment through a Training Program on the Development of Google Sites–Based Educational Websites at SMAN 2 South Bengkulu, Indonesia - Dewi Jumiarni; Prendi Niki Halhaji; Yennita; Rendi Zulni Ekaputri; Dina Qorisah (Aktual: Jurnal Pengabdian Kepada Masyarakat, 2026)
Background: SMAN 2 Manna, South Bengkulu, has teachers with a high level of educational background and adequate school facilities; however, technology has not yet been optimally integrated into the teaching and learning process.Objectives: This community service activity was conducted to improve the understanding and skills of teachers at SMAN 2 South Bengkulu in using Google Sites for teaching.Methods: This community service activity was carried out at SMAN 2 South Bengkulu with 30 teachers as participants. The training program consisting of three stages: preparation, implementation, and evaluation.Result: The implementation of this community service program significantly improved the knowledge and skills of teachers at SMAN 2 Manna, South Bengkulu. Based on the evaluation results obtained through the questionnaire, the score increased from 20.67 in the pretest to 92 in the posttest, with an N-gain value of 0.90, which is classified in the high category.Conclusion: The training program was highly effective in enhancing teachers’ competence in utilizing digital technology in learning. Therefore, it is expected that teachers will be able to implement website-based learning using Google Sites in their teaching practices, thereby supporting the realization of digital transformation in the school.